Content validity of the NECPAL CCOMS-ICO© in Spanish to identify palliative needs in children and adolescents with Cancer - López Alba, Julián Alberto; Jaramillo García, Diana Marcela; Reina Gamba, Nadia Carolina (Investigación y Educación en Enfermería, 2023)
Objective: To perform content validation of the NECPAL CCOMS-ICO© instrument to identify palliative needs in Colombian children and adolescents from 8 to 17 years of age with cancer. Methods. Psychometric study, which used the Lawshe model, modified by Tristan, to perform content validity of the NECPAL CCOMS-ICO© instrument through expert consensus. Results. The Surprise Question (SQ) Would it surprise you if this patient died within the next year? and the parameters Demand: Has there been any implicit or explicit expression of limitation of therapeutic effort or demand for palliative care from the patient, family, or team members?, Need: identified by professional members of the team, Checklist symptoms (ESAS) ≥ 2 persistent or refractory symptoms, Emotional Distress Detection (EDD) > 9, Social and family assessment”, Oncological disease (advanced metastatic or locoregional cancer), Oncological disease (in progression (in solid tumors) and Oncological disease (Persistent symptoms poorly controlled or refractory despite optimizing specific treatment), were considered valid by the experts to identify palliative needs in Colombian children and adolescents aged 8 to 17 years with cancer according to the Lawshe criteria, as modified by Tristán. Parameters specifically related to the oncological disease belonging to the dimension Indicators of severity/progression of the disease showed the highest CVR’ per parameter, with indices of agreement between 0.714 and 0.857. Conclusion. The content of the NECPAL CCOMS-ICO © 3.1 instrument is valid to identify palliative needs in Colombian children and adolescents from 8 to 17 years of age with cancer with a CVI of 0.68.